Pendidikan gizi dan pesan gizi melalui short message service terhadap pengetahuan, perilaku, dan kepatuhan ibu hamil minum tablet besi - Mars Khendra Kusfriyadi; Hamam Hadi; Anis Fuad (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Low compliance as one cause of high prevalence of anemia in Indonesia is mainly due to forgetfulness. Nutrition education and short message service (SMS) are expected to become media to send nutrition message and remind pregnant mothers of taking iron tablet.Objective: To identify impact of nutrition education and nutrition message through SMS to knowledge, behavior and compliance of pregnant mothers with taking iron tablet.Method: The study was a quasi experiment that used pre and post test control/non equivalent control group design involving 3 groups of experiment, i.e. nutrition education only, nutrition education and SMS, and control as comparator. Subject of the study consisted of 121 pregnant mothers. The study was carried out from November 2009 to April 2010 at Palangka Raya Municipality in Pahandut, Kayon and Tangkiling Health Centers. Statistical analysis was performed by using paired t-test, ANOVA, Tukey test, and multivariate test.Results: Pregnant mothers that got nutrition education and SMS intervention significantly improved their knowledge and behavior (p<0.05). Pregnant mothers that got nutrition education and SMS had knowledge 18 point higher (coef=18.26), behavior 4 point better (coef=4.07) and probability 4 times more compliant than the control group (OR=3.79; p=0.03). Nutrition education and SMS intervention could increase compliance and significantly affect increase of hemoglobin (Hb) level up to 1.3g/dl (p<0.05). Increase of Hb level went in line with increase of compliance (dose-response) in pregnant mothers with preliminary Hb level <11g/dl. Meanwhile in pregnant mothers with preliminary Hb level ≥11g/dl, increase of Hb level was statistically significant when compliance reached ≥90%. Conclusion: Pregnant mothers that got nutrition education and SMS had better knowledge, behavior and compliance with taking iron tablet than those that only got nutrition education and the control group. High compliance could significantly increase Hb level.